PENERAPAN LITERASI SAINS DALAM PEMBELAJARAN IPA UNTUK CALON GURU SD - Harlinda Syofyan; Trisia Lusiana Amir (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2019)
Literacy is a complex process, which involves the formation of prior knowledge, culture, and experience to develop new knowledge and deeper understanding. Science literacy is the ability to understand science, communicate science, and apply the ability of science to solve problems. To improve the ability of scientific literacy in addition to requiring student motivation, teachers also need to consider learning strategies that are appropriate to the conditions and potential of students which in the learning process focuses on providing direct experience and the application of the nature of science. Science literacy exists to shape mindsets, behavior, and build human character to care and be responsible for himself, society, and the universe. Literacy learning in schools is carried out to achieve certain goals, but with the development of literacy times it is intended that students are able to achieve certain competencies, so as prospective school teachers who will face 21st century education, 21st century competencies that must be mastered are high-level understanding competencies, competencies critical thinking, collaborative and communicating competencies, and creative thinking competencies. The simulation method is used in the application of scientific literacy using the STL (Science Technology Literacy) method which consists of several stages, namely the contact, curriculum, elaboration, decision making, nexus, and evaluation stages. The results obtained are that the application of the simulation results obtained an average student assessment reached 82.3% with a total of students getting a very good grade of 60% and the rest good at 40%.